Intimate Justice: A Critical Analysis of Sexual Satisfaction - McClelland, Sara I. (Social and Personality Psychology Compass, 2010)
This article elaborates an intimate justice framework to help guide research on sexual satisfaction. Using a critical historiography approach, I examine the etiology and development of the psychological construct of “satisfaction” over the last century and argue that social and political antecedents to satisfaction ratings are an essential and under-theorized aspect of research in this field. By examining what are considered to be the most influential definitions in life satisfaction research, I identify conceptual gaps, oversights, and disagreements that characterize this body of work, and specifically its theoretical treatment of inequity. Moving to the intimate domain, I argue that the field of sexual satisfaction must include theories and methods that systematically consider the role of social and sexual stigmas as antecedents to sexual satisfaction ratings. In the conclusion, building from existing social justice theories, I propose an intimate justice framework as a means to guide research that can highlight issues of entitlement and deservingness in sexual satisfaction research. This is particularly important as sexual satisfaction is increasingly used as an indicator of individual and relational well-being; however, this construct is presently limited and inadequately measured for women and men who experience limited sexual rights in the socio-political domain because of their gender and/or sexual minority status.
Keywords: approches et analyses; capacitisme; cours; discipline; intersectionnalité; justice sociale; premier cycle; psychologie; racisme; ressource en ligne; sciences humaines; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques

The impact of culture and minority status on women's experience of domestic violence - Kasturirangan, Aarati; Krishnan, Sandhya; Riger, Stephanie (Trauma, violence & abuse, 2004)
The influence of culture and ethnic background on women’s experience of domestic violence has been explored in research only recently. Here the authors review research about the impact of culture and minority status in the United States on women’s experience of domestic violence, considering family structure,immigration, acculturation, oppression, and community response. The authors encourage researchers and service providers to acknowledge the effects on women of sociopolitical dynamics, including racism, and to identify specific aspects of culture that are relevant to intimate partner abuse.
Keywords: amériques; approches et analyses; cours; discipline; intersectionnalité; justice sociale; pauvreté; premier cycle; psychologie; racisme; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Project Implicit
Test de préjugés inconscients
Keywords: approches et analyses; biais inconscients; cours; discipline; discours dominant; formations; inégalités; outils; pol5480; premier cycle; privilèges; psychologie; pédagogie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences